Democracia e instituições informais nos partidos políticos brasilieros - Souza, Fabiana Cristina dos Santos (2024)
The thesis aims to comparatively analyze Brazilian political parties regarding their organizational structure, aiming to understand internal democracy based on two axes: inclusivity and formality in the selection of candidates and party leaders. The research intends to address two gaps in the study of party organization in Brazil. Firstly, it seeks to comparatively assess the degree to which party statutes reflect the reality of internal party life, thereby identifying the actual dynamics of Brazilian party functioning. Secondly, it aims to understand how internal democracy is associated with the level of informality within party organizations, highlighting deficiencies in analyses that focus solely on the formal characteristics of these organizations. The guiding question of the thesis is: Do more formal internal processes encourage parties to be more democratic? To answer this question, the proposed research will utilize the first national survey conducted with party members. Subsequently, building on the results of the initial survey, the research aims to investigate how internal democracy correlates with varying degrees of informality, using a binomial logistic regression model. Finally, the thesis proposes a typology to classify the analyzed parties into: 1) Formal Inclusive, 2) Informal Inclusive, 3) Formal Hegemonic, and 4) Informal Hegemonic categories. Additionally, we included a specific analysis of women’s perceptions within the parties, exploring how they evaluate selection processes and opportunities for party participation. This focus allowed us to identify gender nuances that reveal how informal practices and structural barriers impact inclusion and internal democracy, contributing to a broader understanding of the organizational dynamics of political parties in Brazil.